Digital Technology Adoption and Voter Participation: A Systematic Review of Uneven Effects - Sugiono Sugiono; Binana Naz Srulin (JOURNAL OF GOVERNMENT SCIENCE, 2026)
The rapid adoption of digital technology has transformed democratic processes, particularly in shaping electoral participation. However, existing studies report inconsistent and often contradictory findings regarding its impact, largely due to the assumption of uniform effects across different contexts. This study addresses this gap by systematically examining how digital technology produces uneven effects on voter participation. In this study, digital technology is defined as digitally networked tools that mediate political information and engagement, including social media platforms, digital campaigning infrastructures, and algorithm-driven communication systems. Voter participation is conceptualized primarily as electoral engagement, encompassing voter turnout, voting intention, and participation in election-related activities. This study employs a systematic literature review approach, analyzing empirical articles published between 2020 and 2025 from Scopus, JSTOR, and DOAJ databases. A structured protocol based on PRISMA guidelines was used to ensure transparency and rigor in the selection, extraction, and synthesis processes. The findings reveal that digital technology exerts diverse and context-dependent effects on voter participation. While it can enhance engagement through increased access to information and mobilization, it can also generate demobilizing outcomes through misinformation, polarization, and declining trust. These effects are not uniform but are shaped by the interaction of individual factors (e.g., age and digital literacy), technological characteristics (e.g., platform affordances and algorithmic curation), and contextual conditions (e.g., institutional trust and governance quality). This study contributes to digital democracy scholarship by advancing the concept of uneven effects as a central analytical framework for understanding how digital environments reshape electoral participation. It demonstrates that digital technology functions as a conditional force that can both expand and constrain democratic engagement, depending on how structural inequalities are mediated within digital ecosystems. Practically, these findings highlight the need for policies that reduce digital inequalities, strengthen digital literacy, and improve governance frameworks to support more inclusive electoral participation.